1963
DOI: 10.1002/cpt196343315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacologic observations of the effects of ajmaline in chronic atrial fibrillation

Abstract: AjmaTine, an alkaloid which contains the quinuclidine ring, is closely related to quinidine; in quinidine, the quinuclidine ring is joined to quinoline, while in ajmaline, which is derived from a species of Rauwolfia, it is combined with the reputedly less toxic indole nucleus. Ajmaline was administered by slow intravenous drip to patients with chronic, sustained atrial fibrillation, some of whom also had frequent premature ventricular sY5toles. Small doses of ajmaline eliminated the premature ventricular syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Ajmaline has been found effective against experimental and clinical atrial and ventricular arrhythmias (Arora & Madan, 1956;Dick & McCawley, 1963;Bazika et al, 1966;Bojorges et al, 1975;Obayashi et al, 1976;Wellens et al, 1980;Sethi et al, 1984). In the present study we have shown that ajmaline protects against ischaemia-induced arrhythmias in a dose-related manner in anaesthetized rats.…”
Section: Discussionsupporting
confidence: 67%
“…Ajmaline has been found effective against experimental and clinical atrial and ventricular arrhythmias (Arora & Madan, 1956;Dick & McCawley, 1963;Bazika et al, 1966;Bojorges et al, 1975;Obayashi et al, 1976;Wellens et al, 1980;Sethi et al, 1984). In the present study we have shown that ajmaline protects against ischaemia-induced arrhythmias in a dose-related manner in anaesthetized rats.…”
Section: Discussionsupporting
confidence: 67%
“…For this reason, it is a constituent of flower perfumes, pharmacologically active indole alkaloids, and some animal hormones or neurotransmitters such as serotonin [ 271 ] and melatonin [ 272 ]. Some naturally occurring indole alkaloids have gained FDA approval, including vincristine, vinblastine, vinorelbine, and vindesine for its anti-tumor activity [ 273 , 274 ], ajmaline for its anti-arrhythmic activity [ 275 - 277 ], and physostigmine for glaucoma [ 278 ]. Taking inspiration from these natural compounds, several synthetic drugs were synthesized having reached the patient's bedside, such as indomethacin (NSAID) [ 279 ], ondansetron (chemotherapy-induced nausea and vomiting) [ 280 ], fluvastatin (hypercholesterolemia) [ 281 ], zafirlukast (leukotriene receptor antagonist) [ 282 ], etc.…”
Section: Indole Derivativesmentioning
confidence: 99%
“…Ajmaline, a rauwolfia alkaloid, belonging to the large group of indole alkaloids was first isolated and described chemically by Siddiqui & Siddiqui (1931). Subsequently, it was found to be effective against experimental and clinical atrial and ventricular arrhythmias (Arora & Madan 1956;Dick & McCawley 1963;Wellens et a1 1980;Sethi et a1 1984). These studies have established the use of this drug as a class I antiarrhythmic agent with actions similar to those of quinidine.…”
mentioning
confidence: 99%